Knjižna čajanka princes in princev - Litrop, Nataša (Šolska knjižnica, 2012)
Special attention at our school is dedicated to reading literacy and teaching of competences (linguistic and social). Within this we used the School library month for a much-noticed activity including on the one hand children creativity, imagination, innovativeness, aesthetic pleasure, and on the other our goal of establishing quality personal relationships and co-operation of younger and older children, namely voluntary work.
Keywords: bralna kultura; bralna pismenost; branje; jezikovne kompetence; motivacija; osnovne šole; socialne kompetence; šolske knjižnice